A retrospective case series of the treatment of spontaneous quadriceps tendon rupture in patients with uremia and secondary hyperparathyroidism - Wu, Shuang; Wang, Huihui; Zhu, Yanlin; Fu, Weili (Frontiers in Surgery, 2023)
Abstract Background: Spontaneous quadriceps tendon rupture (QTR) is a rare complication of uremia. Secondary hyperparathyroidism (SHPT) is considered the leading cause of QTR in uremia patients. QTR in patients with uremia and SHPT are treated with active surgical repair along with the treatment of SHPT using medication or parathyroidectomy (PTX). The impact of PTX for SHPT on tendon healing remains unclear. The purpose of this study was to introduce surgical procedures for QTR and to determine the functional recovery of the repaired quadriceps tendon (QT) after PTX. Methods: Between Jan 2014 and Dec 2018, eight uremia patients underwent PTX after a ruptured QT was repaired by figure-of-eight trans-osseous sutures with an overlapping tightening suture technique. Biochemical indices were measured before and one year after PTX to evaluate the control of SHPT. The changes in bone mineral density (BMD) were determined by comparing X-ray images at pre-PTX and during follow-up. The assessment of the functional recovery of the repaired QT was conducted at the last follow-up using multiple functional parameters. Results: Eight patients (fourteen tendons) were retrospectively evaluated at an average follow-up of 3.46 ± 1.37 years after PTX. ALP and iPTH levels one year after PTX were significantly lower than at pre-PTX (P=0.017, P＜0.001, respectively). Although there was no statistical differences compared to pre-PTX, serum phosphorus levels decreased and returned to normal one year after PTX (P=0.101). BMD significantly increased at the last follow-up compared to pre-PTX. The average Lysholm score was 73.5 ± 11.07 and the average Tegner activity score was 2.63 ± 1.06. The active knee ROM after repair averaged an extension of 2.85 ± 3.78° to a flexion angle of 113.21 ± 10.12°. The quadriceps muscle strength was grade IV and the mean Insall-Salvati index was 0.93 ± 0.10 in all of the knees with tendon ruptures. All patients were able to walk without external help. Conclusions: Figure-of-eight trans-osseous sutures with an overlapping tightening suture technique is an economical and effective treatment for spontaneous QTR in patients with uremia and SHPT. PTX may promote tendon-bone healing in patients with uremia and SHPT.